2022
DOI: 10.1111/ijd.16080
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hydrotherapy, spa therapy, and balneotherapy for psoriasis and atopic dermatitis: a systematic review

Abstract: Background Atopic dermatitis (AD) and psoriasis are chronic inflammatory diseases that have significant skin complications. Objective The purpose of this systematic study was to evaluate the evidence obtained from human studies on the effects of hydrotherapy, spa therapy, and balneotherapy in psoriasis and atopic dermatitis. Methods The present systematic review was conducted according to the guidelines of the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) statements. Also, for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
7
0
1
Order By: Relevance
“…In 2018, Fioravanti et al demonstrated the efficacy of BT in patients with fibromyalgia by using the thermal water of Vetriolo (Trento, Italy), which descend from the Vetriolo spring in the thick of the fir woods at an altitude of 1500 m. Indeed, Vetriolo’s water is a highly mineralized (fixed residue at 180 °C 1702 mg/L) strongly acidic (pH 5.7) sulfate (1100 mg/L) water that is rich in calcium (111.0 mg/L), magnesium (65.5 mg/L), and iron (315 mg/L) [ 70 ]. Several studies have indicated the efficacy of BT with natural mineral water for psoriasis and atopic dermatitis [ 71 ].…”
Section: Beneficial Effects Of Nitrodi’s Water: Ongoing Datamentioning
confidence: 99%
“…In 2018, Fioravanti et al demonstrated the efficacy of BT in patients with fibromyalgia by using the thermal water of Vetriolo (Trento, Italy), which descend from the Vetriolo spring in the thick of the fir woods at an altitude of 1500 m. Indeed, Vetriolo’s water is a highly mineralized (fixed residue at 180 °C 1702 mg/L) strongly acidic (pH 5.7) sulfate (1100 mg/L) water that is rich in calcium (111.0 mg/L), magnesium (65.5 mg/L), and iron (315 mg/L) [ 70 ]. Several studies have indicated the efficacy of BT with natural mineral water for psoriasis and atopic dermatitis [ 71 ].…”
Section: Beneficial Effects Of Nitrodi’s Water: Ongoing Datamentioning
confidence: 99%
“…Besides, a recent narrative review evidenced a great positive effect of balneotherapy on psoriasis and atopic dermatitis and other dermatological conditions and diseases such as pruritus, prurigo, lichen ruber planus, acne vulgaris, and seborrheic dermatitis (Cacciapuoti et al 2020 ). In addition, a recent systematic review demonstrated the potential positive effects of balneotherapy on dermatological diseases, but it was focalized on specific conditions such as psoriasis and atopic dermatitis (Moini Jazani et al 2023 ). In our knowledge, no recent systematic review summarizes the scientific evidence on balneotherapy and all the known dermatological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options include ointments and moisturizing creams to prevent itchiness, topical corticosteroids, vitamin D analogues, calcineurin inhibitors, phototherapy, keratolytics, and biological monoclonal antibodies (especially in the most severe cases of psoriatic arthritis) [ 3 , 7 17 ]. Short-term balneotherapy with thermal spring water constitutes a valid and proven adjuvant treatment of psoriatic lesions [ 18 ]. However, the mechanisms underlying the beneficial effect of thermal water on psoriatic lesions are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%